Analysis of Energy Spectrum and Wave Function of Modified Poschl Teller Potential Using Hypergeometry and Supersymmetry Method - Solikhah, Fuzi Marati; Suparmi, Suparmi; Variani, Viska Inda (IPTEK The Journal for Technology and Science, 2012)
Modified Poschl Teller potential is a potential model used to describe behavior of inter moleculer forces. The spectrum energy and wave function of the particle affection in modified Poschl Teller potential are obtained by solving the Schrodinger equation, using hypergeometric equation and supersymmetric method. The energy spectrum and wave function are obtained from hypergeometric equation, which is constructed from Schrodinger equation through variable substitution. The energy spectrum and wave function are obtained using raising and lowering supersymmetric operator and applying shape invariance property. The solution of those equation of the energy spectrum and wave function obtained using these two methods are exact solution. Further, the wave function and density probability are visualized using computer simulation.